RETRACTED: The importance of using information and measurement systems in the process of environmental monitoring in the Russian Federation - Yakovlev Valeriy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001